2016
DOI: 10.1016/j.cell.2016.11.046
|View full text |Cite
|
Sign up to set email alerts
|

Linking the Human Gut Microbiome to Inflammatory Cytokine Production Capacity

Abstract: SummaryGut microbial dysbioses are linked to aberrant immune responses, which are often accompanied by abnormal production of inflammatory cytokines. As part of the Human Functional Genomics * Correspondence: xavier@molbio.mgh.harvard.edu (R.J.X.), mihai.netea@radboudumc.nl (M.G.N.). Lead ContactPublisher's Disclaimer: This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the manuscript. The manuscript will unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
203
0
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 230 publications
(207 citation statements)
references
References 29 publications
1
203
0
3
Order By: Relevance
“…The accompanying study by Yang et al demonstrates that genetic variability of the host has a strong effect on cytokine responses, again with the impact depending on the type of pathogen and cytokine studied (Li et al, 2016). In addition, a role of non-genetic factors for the modulation of cytokine responses is supported by the identification of important microbiome components that modulate cytokine responses, as described in the accompanying manuscript by Schirmer et al (Schirmer et al, 2016). These effects are likely mediated by microbial components, or through diverse metabolites released by microbiota-diet interaction.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The accompanying study by Yang et al demonstrates that genetic variability of the host has a strong effect on cytokine responses, again with the impact depending on the type of pathogen and cytokine studied (Li et al, 2016). In addition, a role of non-genetic factors for the modulation of cytokine responses is supported by the identification of important microbiome components that modulate cytokine responses, as described in the accompanying manuscript by Schirmer et al (Schirmer et al, 2016). These effects are likely mediated by microbial components, or through diverse metabolites released by microbiota-diet interaction.…”
Section: Discussionmentioning
confidence: 99%
“…We systematically investigated the factors that influence the human cytokine responses in the 500 Functional Genomics (500FG) cohort of healthy volunteers within HFGP, after stimulation of their leukocytes with bacterial, fungal, viral and non-microbial metabolic stimuli; while the present study assessed the impact of environmental and non-genetic host factors on cytokine responses, complementary studies investigated the impact of the genetic (Li et al, 2016) and microbiome (Schirmer et al, 2016) variability on cytokine production.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Conversely, dysbiosis in the gut has been linked to the subsequent hospitalization of patients with sepsis, which suggests an association between the composition of the gut microbiota and sepsis susceptibility 74 . The composition of the gut microbiome of healthy individuals influences cytokine release by blood leukocytes in a stimulus-specific and cytokinespecific way 75 . Preclinical studies have demonstrated that disruption of the gut microbiome by broad-spectrum antibiotics impairs host defence during sepsis, and this impairment might be due to several mechanisms [76][77][78] .…”
Section: The Microbiome In Sepsismentioning
confidence: 99%